Aproveitamento da massa visceral da tilápia (Oreochromis niloticus) para produção de biogás - Soethe, Geovan Carlos (2014)
This study presents itself as a sustainable alternative to fish tailing on the possibilities of energy generation in the form of biogas . The experiment was delimited in the city of Foz do Iguaçu - PR , with local sampling of specimens from the viscera of Nile tilapia ( Oreochromis niloticus ) . The physicochemical properties of the viscera in natura were evaluated in parallel performed in batch fermentation in a period of 56 days, verifying their potential to generate biogas ( CH4 ) , as a way of harnessing this disposal . The characterization of the viscera in natura , the total solids ST ( g ) , volatile solids SV ( g ) , solid fixed SF ( g ) , biochemical oxygen demand BOD ( mg l- 1 ) and chemical demand were evaluated oxygen COD (mg L -1) macro and micro nutrients as well as the amount of fat present HQ ( gL -1). In the experi-mental phase visceral tailings were ground, sieved , mixed and arranged in ascending order of four treatments : T1 ( 25 % ) , T2 50 % , T3 75 % and T4 100 % , mixed in co -digestion with swine manure in concentrations of 4.67% , 5.72 % , 6.15 % , 7.44 % to ST added and 3.73% , 4.80 % , 5.40 % , 5.43 % to VS added , respectively for the four treatments, with an inoculum volume of 20%. The results obtained by physicochemical characterization of the viscera sho-wed favorable results for the production of biogas , such as pH between 6.27 and 7.02 , SV and SF concentration of 91.64 % and 8.33 % , and also some restrictions as dispersions in micro and macro levels of nutrients C: N: P : S of 525,10:15,90:6,00:22,51 (GL- 1 ), respecti-vely, the amount of fat ( 20.02% ) and high levels of BOD and COD in mg l- 1 and 129,525.00 503,750.00 mg.L - 1 . In their experimental stage T1 , T2 , T3 and T4 resulted in consumption of 21.98 % , 34.56 % , 16.63% , 28.77 % and effluent STF 21.54 % 39.73 % , 16.26% , 26.34 % STV - effluent. There were also variations in pH , with a penchant for T1 and T3 and a tendency to neutralization in the T2 and T4 , and in the period of analysis CH4 concentrations up to 88.72 % .